(untitled) - Haag, Stephen (Boston, Mass., 2005)
This text offers chapters that cover what instructors want students to know about MIS. The Extended Learning Modules (XLMs) show students what they can do with MIS. The instructor controls the mix by picking the chapters and XLMs to include in the course. A contemporary writing style and a wealth of examples engage students like no other MIS text
Keywords: Management information systems,Hệ thống thông tin quản lý,Information technology,Công nghệ thông tin